Comparative genomics and genome biology of Campylobacter showae. Issue 1 (1st January 2019) - Hsu, Tiffany; Gemmell, Matthew R.; Franzosa, Eric A.; Berry, Susan; Mukhopadhya, Indrani; Hansen, Richard; Michaud, Monia; Nielsen, Hans; Miller, William G.; Nielsen, Henrik; Bajaj-Elliott, Mona; Huttenhower, Curtis; et al.
ABSTRACT: Campylobacter showae a bacterium historically linked to gingivitis and periodontitis, has recently been associated with inflammatory bowel disease and colorectal cancer. Our aim was to generate genome sequences for new clinical C. showae strains and identify functional properties explaining their pathogenic potential. Eight C. showae genomes were assessed, four strains isolated from inflamed gut tissues from paediatric Crohn's disease patients, three strains from colonic adenomas, and one from a gastroenteritis patient stool. Genome assemblies were analyzed alongside the only 3 deposited C. showae genomes. The pangenome from these 11 strains consisted of 4686 unique protein families, and the core genome size was estimated at 1050 ± 15 genes with each new genome contributing an additional 206 ± 16 genes. Functional assays indicated that colonic strains segregated into 2 groups: adherent/invasive vs. non-adherent/non-invasive strains. The former possessed Type IV secretion machinery and S-layer proteins, while the latter contained Cas genes and other CRISPR associated proteins. Comparison of gene profiles with strains in Human Microbiome Project metagenomes showed that gut-derived isolates share genes specific to tongue dorsum and supragingival plaque counterparts. Our findings indicate that C. showae strains are phenotypically and genetically diverse and suggest that secretion systems may play an important role in virulence potential.